Unveiling the journey: a deep dive into healthcare workers’ preparation, concerns, and experiences with the COVID-19 vaccine- a qualitative study - Panigrahi, Sasmita; Sadhana Priyadarshani, N.; N., Nadikrishnan; Henry, Kalaivani; Parida, Swayampragnya (International Journal of Research in Medical Sciences, 2025)
Background: The COVID pandemic had a profound impact on human life globally and presents an unprecedented challenge to public health, food systems, and the world of work. The COVID vaccine is considered as safe and effective for minimising the impact of COVID-19. However, vaccine related adverse event is one of the major reason for vaccine scepticism. Therefore, this study intended to explore post COVID vaccine related adverse effects and concerns among HCWs. Methods: A qualitative exploratory study was conducted among HCWs of a tertiary care centre, eastern India, who developed vaccine related adverse effects within 7 days of receipt of COVID vaccine. Information was collected by using indepth interview guide from 12 health care professionals. Then, the data was transcribed, systematically coded and analyzed following the thematic framework approach using MAXQDA-2020 software. Results: After the analysis four main themes were emerged: vaccination perception and readiness; post vaccination aftermath; management of adverse effects; suggestions. Respondents across the demographic group depicted varied concerns and experiences like they received vaccine to motivate other, be part of research and the vaccination. The most common reported adverse events wererange from headache, body ache, fever, altered taste, dizziness to hyperglycemia, irregular heart rate, diarrhoea and dyspnea. Moreover, their experience from first dose of vaccine convinced them to prepare for the 2nd dose with taking adequate fruit, water and rest. Conclusions: Knowledge about people’s lived experiences and their concerns after receiving COVID-19 vaccine can be used to formulate strategies and awareness programmes to enhance the vaccine uptake in future.